Thematic choice in selected Malaysian Malay women’s short stories: a representation of Malaysian Malay female identity from a systemic functional perspective - Tan, Swee Mee (2023)
Using a systemic functional analysis of three selected stories written by three different Malay women writers, namely Che Husna Azhari, Dina Zaman and Karina Bahrin, the study explores a representation of the Malay women’s identity from two contrasting settings, two kampongs in the East coast of Malaysia, Kelantan and Terengganu respectively and an urban Kuala Lumpur cosmopolitan. The study interprets the social cultural identity of Malay women within a linguistic context based on an analysis of thematic choice from the Hallidayan notion of grammar, more specifically, the System of Theme and Rheme and the resources of the System of Transitivity. In Mariah, a perfect Muslim world was construed by Che Husna Azhari because of Cik Yam’s submission and Mariah’s giving way to the Imam to become a subordinate role in the story. In And She Became an Angel (Dina Zaman), suggesting a subordinated female identity in a Malay kampong context, Mandak transposes a victimized role, a barren woman who bravely sought for a life transformation to become the heroin of the story, a western look angel. As in A Subtle Degree of Restraint (Karina Bahrin), Elena and Badariah, two representations of urban Malay women living in Kuala Lumpur, iv experienced a subtle deprivation of liberty in the contrasting life condition of either marriage or barrenness. They were the representation of two different types of new highbred Malaysian Malay women bestowed by a rapid globalized cosmopolitan Kuala Lumpur. Consolidated with the notion of feminist study and Critical Discourse Analysis in the discussion of Malaysian Malay women’s identity, this study also proves that Hallidayan framework is a resourceful analytical tool in the exploration of text as a piece of social semiotic from the angles of Field, Mode and Tenor. The study also reveals that in the eyes of Malay women writers, Malay women have evolved from a silenced representation in the pioneering decades of the Malaysian Literature to a visible and vocal delegation who stood out with their own unique expression of life experiences from the clausal base analysis.